Pengembangan Instrumen Tes Keterampilan Berpikir Kritis Berbasis G-Form pada Materi Asas Black: Pengembangan Instrumen Tes Keterampilan Berpikir Kritis Berbasis G-Form pada Materi Asas Black - Ramadhana Zsa Zsa Alifah, Dea; Sunarti, Titin (IPF: Inovasi Pendidikan Fisika, 2024)
A good instrument is an instrument that has theoretical (according to experts) and empirical feasibility (empirical trials). Theoretical feasibility obtained validity according to three experts, and empirical feasibility obtained validity of the question items; the power of different questions that can differentiate smart and not smart students; also the level of difficulty of the questions (not difficult and not easy) that meets the criteria. The aim of this research is to analyze feasibility theoretically and empirically. The research method used is a test item validity instrument to obtain theoretical feasibility, and empirical trials to obtain empirical feasibility. Data collection techniques include validation techniques and test techniques. 105 students divided into three classes answered 5 questions on basic black material according to the indicators of critical thinking skills on the G-Form which were then analyzed. The results of this research are that theoretically from three experts the instrument used is very valid, empirically the results of the trial are seen from the test scores which are then analyzed per item, resulting in the validity of the instrument being categorized as valid, the differentiating power of the questions being categorized as good, and the level of difficulty of the questions being categorized as moderate. Based on the research results, it can be concluded that the critical thinking skills test instrument based on G-Form on basic black material is suitable for use. Keywords: Question differentiation, critical thinking skills, question difficulty level, and validity